Studies on Neotropical crickets: The continental Otteiini taxa (Orthoptera: Phalangopsidae), those cave crickets are not confined to the West Indies - Cadena-Castañeda, Oscar J.; Soto, Wolfang Andrés Rodríguez; Cárdenas, Andrea Del Pilar Floréz; Acevedo, Angélica (Zootaxa, 2021)
The tribe Otteiini is a group of cave crickets, that were believed only to inhabit the Greater Antilles (Cuba, Cayman Islands, and Hispaniola). However, when reviewing and studying similar cave crickets in Mexico, their relationship was proven with island taxa, expanding their distribution to the continental area, from the Yucatan Peninsula to the Gulf and Northeast of Mexico. Herein, the genus Paracophus is divided, and three additional genera are described: Hubbellcophus n. gen., Venegascophus n. gen. and Hortacophus n. gen. Also, two additional species for Paracophus are described (P. victoriensis n. sp. and P. velazquezi n. sp.). Diagnoses for all genera and dichotomous keys for genera and species are provided. Finally, the taxonomic relationships between the insular and continental taxa of the tribe are discussed, and the different taxonomic placements they had over time, with some genera located in Phalangopsinae and Luzarinae (Phalangopsidae) and Pentacentrinae (Gryllidae).